How do Entrepreneurial Bosses influence their Employees' Future Entrepreneurship Choices? - Vera Rocha; Mirjam van Praag (Tinbergen Institute, 2016)
We adopt a process-based approach to investigate the influence of entrepreneurial bosses on the two main decisions of employees towards becoming entrepreneurs: exit from the current firm and entry into entrepreneurship. In other words, we study the push and pull mechanisms possibly underlying the influence of entrepreneurial bosses. We do so by employing an identification strategy based on comparisons of same-gender matches of bosses and employees, using rich register data for Denmark. We show that same-gender entrepreneurial bosses have a great impact on employees' future entrepreneurship choices, especially among women. We do not find any evidence that female bosses push female employees out of the workplace, by creating a discriminatory environment that forces them to search for alternative career paths. Instead, our analysis finds consistent support for pull mechanisms, with role modeling being the main explanation for the positive influence of female entrepreneurial bosses on female employees' transition into entrepreneurship. We show that the female boss effect is greater than other social interactions identified in prior research. We conclude that entrepreneurial bosses can be role models and female entrepreneurial bosses may thus act as a lever to reducing gender gaps in entrepreneurship rates.
Keywords: J19; J24; L26; M12; M13; 330; Entrepreneurship; role models; gender gaps; female leadership